FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN KAP - Titis Bonang Abdillah; Arifin Sabeni (Diponegoro Journal of Accounting, 2013)
Independence of the public accounting firm will fade when the suspect had long-standingrelationships with its clients. One way to keep independence auditor is to make the turnpublic accounting firm. Several previous studies showed the results of different studies.This study aims to examine and obtain empirical evidence about the factors that affect thecompany went public did turn public accounting firm in Indonesia. Factors used includemanagement stock ownership, dividend policy, financial distress, the number ofcommissioners, management changes, going-concern opinion, and audit tenure. This studyis a population of companies listed on the Stock Exchange in the year 2009-2012. The totalsample is 116 using purposive sampling. Hypothesis testing is performed using logisticregression using SPSS 16 application. The results of this study are dividend policy andtenure have significant effect on the change of KAP on manufacturing companies inIndonesia. While other factors such as management ownership, financial distress, thenumber of commissioners, change management and going concern opinion has nosignificant effect on the change of KAP on manufacturing companies in Indonesia.